Design and test of the progressive push-out automatic seedling taking device for vegetable substrate block seedlings - Cui, Zhichao; Fu, Jingjing; Li, Jicheng; Ji, Haibo; Wu, Changhao; Zheng, Shuhe; Xiao, Tiqiong; Chen, Yongsheng; Zhang, Chenghao; Yang, Yating; et al. (International Journal of Agricultural and Biological Engineering, 2025)
Aiming at the problems of low success rate and high seedling injury rate of automatic vegetable transplanting, this study focused on cabbage substrate block seedlings and developed a progressive push-out automatic seedling device controlled by a PLC system. Based on the friction mechanical properties of seedlings-tray during seedling taking, the collision rebound theoretical analysis of substrate block seedling delivery and the finite element simulation analysis of the seedling taking mechanism were carried out to determine the conditions for stable seedling taking and delivery of the device and the working parameters of the key mechanisms. To evaluate individual parameter effects, a test bench was built, and the effective ranges of key factors were subsequently determined. Three key experimental factors, the inclination angle of the limit guide plate, the seedling separation channel width, and the seedling separation cylinder pressure were investigated using an L9(34) orthogonal array design with blockage rate and breakage rate as evaluation metrics. The range and variance analysis methods were employed to determine the relative significance of each factor’s influence on the performance indicators. The optimal parameters were determined as: the inclination angle of the limiting guide plate was 3.5°, the width of the seedling separation channel was 50 mm, and the pressure of the seedling separation cylinder was 0.6 MPa. Under these conditions, the seedling taking effect was significantly improved: the blockage rate was 2.46%, the breakage rate was 3.18%, and the seedling taking success rate was 94.36%. The optimal parameter combination was verified by the experiment: the average blockage rate was 3.23%, the average breakage rate was 3.68%, and the average success rate was 93.09%. Compared with the orthogonal experiment, the relative success rate error was 1.27%, indicating that the device has high stability. This study will provide a reference for the design of automatic vegetable transplanters. Keywords: transplanter, substrate block seedlings, automatic seedling taking device, PLC control system, progressive push-out DOI: 10.25165/j.ijabe.20251804.9346 Citation: Cui Z C, Fu J J, Li J C, Ji H B, Wu C H, Zheng S H, et al. Design and test of the progressive push-out automatic seedling taking device for vegetable substrate block seedlings. Int J Agric & Biol Eng, 2025; 18(4): 89–100.